2013
DOI: 10.1103/physrevd.88.041503
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic mass ejection from black hole-neutron star binaries: Diversity of electromagnetic counterparts

Abstract: The merger of black hole-neutron star binaries can eject substantial material with the mass ∼ 0.01-0.1M⊙ when the neutron star is disrupted prior to the merger. The ejecta shows significant anisotropy, and travels in a particular direction with the bulk velocity ∼ 0.2c. This is drastically different from the binary neutron star merger, for which ejecta is nearly isotropic. Anisotropic ejecta brings electromagnetic-counterpart diversity which is unique to black hole-neutron star binaries, such as viewing-angle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
179
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(194 citation statements)
references
References 52 publications
15
179
0
Order By: Relevance
“…Note that, however, as the outflow is only mildly relativistic, even from a highly a-spherical ejecta, the emission will be roughly isotropic and viewing angle effects will be small. It is worth noting that the effect of a-sphericity is more relevant for black hole neutron star mergers, which can result in highly a-spherical mass ejection (see e.g., Kyutoku et al 2013;Foucart et al 2013). …”
Section: Numerical Resultsmentioning
confidence: 99%
“…Note that, however, as the outflow is only mildly relativistic, even from a highly a-spherical ejecta, the emission will be roughly isotropic and viewing angle effects will be small. It is worth noting that the effect of a-sphericity is more relevant for black hole neutron star mergers, which can result in highly a-spherical mass ejection (see e.g., Kyutoku et al 2013;Foucart et al 2013). …”
Section: Numerical Resultsmentioning
confidence: 99%
“…We will study consequences of our results on the synthesis of heavy elements in the forthcoming paper. If EOS is not very soft like SFHo, some other contributions, such as mergers of black hole-neutron star binaries [38], disk winds from accretion torus around a merger remnant black hole [34,39], and magnetorotational supernova explosions [40] may be necessary. In such cases, however, it is not clear whether the universality requirement can be achieved or not.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The number of simulations studying these mergers and their fates has grown with time (Rosswog et al 2004;Rosswog 2005;Rantsiou et al 2008;Foucart et al 2010Foucart et al , 2011Foucart et al , 2015Kyutoku et al 2013;Paschalidis et al 2014), all showing that the final fate of the merged system depends sensitively upon the initial conditions. Based on earlier merging BH-NS models by Rantsiou et al (2008), it was shown for one particular evolutionary model that only a fraction of BH-NS systems may potentially form an accretion torus and lead to a GRB.…”
Section: Bh-ns Mergersmentioning
confidence: 99%
“…In the past decade, the number of hydrodynamic simulations of NS-NS and BH-NS mergers has grown considerably (Foucart et al 2010(Foucart et al , 2011(Foucart et al , 2015Foucart 2012;Korobkin et al 2012;Hotokezaka et al 2013;Kyutoku et al 2013;Bauswein et al 2014;Kiuchi et al 2014;Radice et al 2014;Shibata et al 2014;Takami et al 2014). Although these models are becoming increasingly sophisticated, most of the current models include only a subset of the physics needed to model these objects: hydrodynamics, neutrino transport (or at least neutrino energy losses), nuclear equations of state, magnetic fields, and general relativity.…”
Section: Merger Modelsmentioning
confidence: 99%